Pemberdayaan Ekonomi Masyarakat Melalui Pengolahan Keripik Pisang di Toko Karya Mandiri - Raditya, Muhammad Ragil; Salsabila, Nala; Gunawan, Prima Sahih; Ramadhan, Raihan; Pratama, Reza Hardian (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The community economic empowerment program through banana chip processing at Toko Karya Mandiri aims to enhance local skills in transforming bananas into value-added products. Through hands-on training in processing and marketing, participants learn to produce high-quality banana chips and develop effective marketing strategies. The program's results show improved technical skills, better understanding of branding, and increased income for the community. Additionally, the initiative successfully created sustainable business opportunities, positively impacting the local economy. This program demonstrates that processing local products like banana chips can be a viable alternative for economic empowerment based on sustainable local resources.